Comoving Distance- Light Travel Distance (Treatise) - Weitter Duckss (Budapest International Research in Exact Sciences (BirEx) Journal, 2020)
The discussion on the values of redshift, as well as blueshift, is based on a large increase in new evidence that in the whole volume of Universe there are gravitationally-bound objects (galaxies, clusters and super clusters of galaxies) „Using the Chandra and Hubble Space Telescopes we have now observed 72 collisions between galaxy clusters, including both ‘major’ and ‘minor’ mergers” (Harvey, 2015). That adds to a great diversity of galactic movement directions and their diverse appearances to an observer. The accent here is at the point of "clearing the early Universe" and asks questions about how these types of radiation could be measured if all galaxies were created in the early stages of Universe, which had started emitting these types of radiation. At the same time, some questions are asked about. With a redshift of 5.47, (Q0906 + 6930) light from this active galaxy is estimated to have taken around 12.3 billion light-years to reach us.. distance to this galaxy is estimated to be around 26 billion light-years (7961 Mpc). (NASA/IPAC, 2010) i.e., why the actual measured values of redshift are not applied.